IMPROVING THE METHODOLOGY OF RESOLVING FAMILY DISPUTES IN CONTROVERSIAL FAMILIES (World Bulletin of Management and Law, 2023)
This article talks about improving the method of ending family disputes in conflicting families. Based on scientific data, the author studied and analyzed the specific aspects of improving the method of ending family disputes in conflicting families based on existing literature.